2017
DOI: 10.1097/inf.0000000000001483
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Mumps Infection Among Children in the Democratic Republic of Congo

Abstract: These data suggest that mumps virus is circulating in DRC and risk of exposure increases with age. At present, the introduction of a combined measles-mumps-rubella vaccine remains unlikely, as the capacity to maintain adequate vaccine coverage levels for routine immunization must be improved before additional antigens can be considered for the routine immunization schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
4
8
1
Order By: Relevance
“…A full immunization coverage as low as 45% suggests that children from the DRC are at high risk of avoidable death. A recent study by Doshi et al showed that Congolese children are already at high risk of measles [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…A full immunization coverage as low as 45% suggests that children from the DRC are at high risk of avoidable death. A recent study by Doshi et al showed that Congolese children are already at high risk of measles [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…DBS samples were extracted using a modified extraction protocol [19] and processed at the UCLA-DRC laboratory at the National Laboratory for Biomedical Research in Kinshasa. The DBS extraction and assay protocol and multiplex technology have been described elsewhere [20]. The Dynex Multiplier chemiluminescent automated immunoassay platform with a research-use-only SmartPLEX assay for measles, mumps, rubella, varicella-zoster virus, and tetanus (Dynex Technologies, Chantilly, Virginia) was used to test samples for immunoglobulin G antibody response.…”
Section: Methodsmentioning
confidence: 99%
“…Efforts to introduce vaccine programs must go along with understanding the epidemiology of the virus. In Africa, only few studies have documented the seropositivity of mumps virus whereby in children aged one month to six years was found to be 9% and 22% in South Africa and Democratic Republic of Congo (DRC), respectively [19,20]. Despite being common in many countries with reported associated complications, there is scarcity of data regarding its epidemiology in Tanzania.…”
Section: Introductionmentioning
confidence: 99%